Determinants of Factors Influencing Food and Beverage Entrepreneur in Using Electronic Money as a Payment Method - Afuan Fajrian Putra; Filza Ramdani (Fakultas Ekonomi dan Bisnis Universitas Papua, 2023)
This study aims to determine what factors can influence business people in food and beverage in using electronic money as a payment method. The variables used include perceives trust (X1), perceived security (X2), perceived ease of use (X3), and perceived usefulness (X4). This study uses primary data which is directly taken from the sample of respondents. The research sample was taken through technique-purposive sampling and calculating the number of samples using the malthotra formula so that a sample of 150 business people is obtained for food and beverage in the area of D.I Yogyakarta. This study uses multiple linear regression analysis techniques. The results of the study show that perceptions of security have a positive and significant influence on the intention to use-money by SMES. Meanwhile, the variables of perceived trust, perceived ease of use, and perceived usefulness are known to not affect the intention to use e-money.